Penanggulangan Dampak Riba Melalui Pendekatan Pendidikan - Sapiudin Shidiq (Qiro'ah : Jurnal Pendidikan Agama Islam, 2018)
The usury is more and more act violently and arbitrarily in society. Its effect not only damages the economic system but also damages the mentality of agent. The pressing, egoism and individulism are sign of the usury badness. If its current can't be minimalized, the usury will cause to collapse the society harmony. Clearly, Islam forbids the usury. The function of Islamic education is doing preventif and kuratif stride